2005
DOI: 10.1108/09578230510625683
|View full text |Cite
|
Sign up to set email alerts
|

Successful school leadership: the Norwegian case

Abstract: PurposeThis paper aims to identify what counts as successful school leadership within a Norwegian context.Design/methodology/approachThe paper uses multi‐site case study methods as a methodological approach. In selecting cases the first strategy included schools appointed as “good practice schools” by the Ministry of Education and Research. The second strategy was to obtain a desired variation based on different factors like school size and structure, rural/urban representation and principals' gender.FindingsL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…The reviewers also realized that there was an apparent distinction in the perspectives of Western and Eastern civilizations towards leadership distribution. Research findings indicate distributive and participative leadership is viewed more positively in the countries representing the Western world (U.S.A, Australia, U.K., New Zealand, Belgium, Malta, Portugal, Norway, Canada) than in the Oriental or East Asian settings (Iran, Pakistan, China, Taiwan, Thailand, Vietnam, South Korea, Hong Kong, Singapore) (Abrahamsen et al, 2015;Arrowsmith, 2007;Harris & Townsend, 2007;Hulpia et al, 2009;2011;Moller et al, 2005;Ritchie & Woods, 2007). The review findings point out that in the Eastern cultures power distance matters a lot and a solo leader is trusted to run the school on behalf of his subordinates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewers also realized that there was an apparent distinction in the perspectives of Western and Eastern civilizations towards leadership distribution. Research findings indicate distributive and participative leadership is viewed more positively in the countries representing the Western world (U.S.A, Australia, U.K., New Zealand, Belgium, Malta, Portugal, Norway, Canada) than in the Oriental or East Asian settings (Iran, Pakistan, China, Taiwan, Thailand, Vietnam, South Korea, Hong Kong, Singapore) (Abrahamsen et al, 2015;Arrowsmith, 2007;Harris & Townsend, 2007;Hulpia et al, 2009;2011;Moller et al, 2005;Ritchie & Woods, 2007). The review findings point out that in the Eastern cultures power distance matters a lot and a solo leader is trusted to run the school on behalf of his subordinates.…”
Section: Resultsmentioning
confidence: 99%
“…Collaboration within "enquiry groups" and holding regular meetings to carry out decision-making processes are identified among the actions taken for sharing leadership functions (Bezzina, 2008;Salfi, 2011). Emerging themes also point out that leadership at schools tend to be distributed to stakeholders, such as parents, teachers, students and wider environment through representation and collaboration in leadership processes (Cowie et al, 2011;Hulpia et al, 2011;Moller et al, 2005;Park & Datnow, 2009;Rah, 2013;Salfi, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The mobility is low, due to practical reasons, such as a challenging geography, and more cultural reasons, such as a tradition of strong local anchoring. On a national level, these demographic and cultural features might also explain why the competition between schools in Norway is fairly weak (Møller et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This principle has resulted in a relatively high number of schools, especially in primary education. Many of these schools are situated in rural areas and have less than 100 pupils (Møller et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A Norwegian study on the characteristics of successful leadership practice in primary and secondary schools indicated that successful school leadership requires team work (Møller, Eggen, Fuglestad, Langfeldt, Presthus, Skrøvset, Stjernstrøm and Vedøy, 2005, as cited in Møller, 2011, p. 121) and "democratic principles and values" (Møller et al, 2005, p. 584). Hallinger and Heck (2010) also found that "collaborative school leadership can positively impact student learning" (Hallinger & Heck, 2010, p. 95).…”
Section: Leadership Styles and Student Academic Achievementmentioning
confidence: 99%